Feasibility of magnetic resonance‐only high‐dose‐rate surface brachytherapy for clinical application. Issue 11 (24th September 2021) - Lee, Casey Y.; Kaza, Evangelia; Devlin, Phillip M.; Cormack, Robert A.; Buzurovic, Ivan
Abstract: Purpose: In this article, we investigate the feasibility of magnetic resonance (MR)‐only imaging for high‐dose‐rate (HDR) surface brachytherapy (SABT). We examined whether a standard CT‐based planning can be replaced with an MR‐only planning. For this purpose, the MRI digitization and plan quality check processes were compared against the standard CT‐based processes. A prospective clinical implementation of the MR‐only planning was evaluated on a clinical data set. Methods: A pointwise encoding time reduction with radial acquisition (PETRA) sequence was optimized for visualization of Freiburg flap (FF) on MR images. MR and conventional CT images were acquired with a FF applicator (Elekta, Stockholm, Sweden) placed on the following phantoms: (1) flat styrofoam (FST), FF locked‐in placed with supporting structure; (2) cast‐made facemask, and (3) porcine leg (PL). Catheters were digitized and activated with 10 mm step size on Oncentra Brachy 4.5.3 Treatment Planning System. The CT‐only and MR‐only treatment plans were generated by optimizing the dose to the target defined as volume at 3 mm skin depth. To compare the plans, the MRI‐to‐CT alignment was performed via rigid registration. Positional displacements of dwell positions between CT and MR plans were compared on the FST phantom and the relative percent dose difference in 2210 different points from CT or MR‐only plans was compared. For all three phantoms, the comparabilities between CT and MR‐only plans were assessed by calculating dice similarity coefficient (DSC) for volumes enclosing 150%, 125%, 100%, 95%, 90%, 80%, and 65% isodose lines ( V 150 − V 65 ). The MR images of FF placed on the forearm of a healthy subject were acquired with this optimized PETRA sequence and used for treatment planning. The relative percent dose was calculated on 140 representative points placed at 3 mm skin depth to evaluate the dose to the skin. Results: Using the optimized PETRA sequence, MRTP digitization accuracy was < 1 mm in each dimension and on three‐dimensional (3D) displacement for the FST phantom. In each phantom and clinical data set, it was possible to generate MR‐only treatment plans with the 3 mm skin depth prescription. In the FST phantom, the mean relative dose at the points was not significantly different (< 0.1% difference) for CT or MR‐based plans. The assessment of similarities in dose profiles between CT and MR‐only plans' provided DSC values greater than 0.96, 0.92, and 0.73 for all volumes enclosing up to 100%, 125%, and 150% isodose lines, respectively. Conclusion: The feasibility of generating a HDR treatment plan with FF using MR‐only has been evaluated in phantoms with varying geometry and for a clinical data set. The optimization of a standard MRI sequence—PETRA—implemented in this study showed that FF‐based catheters can be digitized and a plan can be generated using only MRI. The resulting MR‐only plans were comparable to the conventional CT‐based plans, suggesting that MRI alone can generate clinically acceptable plans for FF in phantoms and on a clinical data set. Reliable MR‐only treatment planning could improve treatment prescription through more accurate characterization of soft tissue targets.